Changes in Bone Mass After Discontinuation of Preexposure Prophylaxis With Tenofovir Disoproxil Fumarate/Emtricitabine in Young Men Who Have Sex With Men: Extension Phase Results of Adolescent Trials Network Protocols 110 and 113. (8th June 2019) - Havens, Peter L; Perumean-Chaney, Suzanne E; Patki, Amit; Cofield, Stacey S; Wilson, Craig M; Liu, Nancy; Anderson, Peter L; Landovitz, Raphael J; Kapogiannis, Bill G; Hosek, Sybil G; Mulligan, Kathleen
Abstract: Human immunodeficiency virus–seronegative men aged 15–22 years who lost bone mineral density (BMD) during tenofovir disoproxil fumarate/emtricitabine preexposure prophylaxis (PrEP) showed BMD recovery 48 weeks following PrEP discontinuation. Lumbar spine and whole body BMD z -scores remained below baseline 48 weeks off PrEP in participants aged 15–19 years. Clinical Trials Registration . NCT01772823 (ATN 110) and NCT01769456 (ATN 113).